2022
DOI: 10.1158/1078-0432.ccr-22-1215
|View full text |Cite
|
Sign up to set email alerts
|

A Cathepsin-Targeted Quenched Activity–Based Probe Facilitates Enhanced Detection of Human Tumors during Resection

Abstract: Purpose: Fluorescence-guided surgery using tumor-targeted contrast agents has been developed to improve the completeness of oncologic resections. Quenched activity-based probes that fluoresce after covalently binding to tumor-specific enzymes have been proposed to improve specificity, but none have been tested in humans. Here, we report the successful clinical translation of a cathepsin activity-based probe (VGT-309) for fluorescence-guided surgery. Experimental Design: We optimized the specificity, dosing, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Enzyme-or pH-activated probes have the potential to address some of these shortcomings as demonstrated by results from phase 2 and phase 3 clinical trials, though none of these probes are FDA-approved at this time. 46,47 Since there is still no universal molecular probe that works for all types of cancers, the next frontier for FGS will involve a cocktail of carefully selected tracers to highlight all tumors and involved lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme-or pH-activated probes have the potential to address some of these shortcomings as demonstrated by results from phase 2 and phase 3 clinical trials, though none of these probes are FDA-approved at this time. 46,47 Since there is still no universal molecular probe that works for all types of cancers, the next frontier for FGS will involve a cocktail of carefully selected tracers to highlight all tumors and involved lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, about 20% of adenocarcinoma patients and the majority of squamous cell and non-small cell lung cancer patients will not benefit from the pafolacianine probe due to a lack of folate alpha receptors in the primary tumors. Enzyme- or pH-activated probes have the potential to address some of these shortcomings as demonstrated by results from phase 2 and phase 3 clinical trials, though none of these probes are FDA-approved at this time 46 , 47 . Since there is still no universal molecular probe that works for all types of cancers, the next frontier for FGS will involve a cocktail of carefully selected tracers to highlight all tumors and involved lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The previously described cathepsin-targeted probe VGT-309 is currently under investigation in a phase II clinical trial in 40 patients undergoing surgery for primary lung cancer or lung metastases (NCT05400226). The preliminary results in two patients have already been published and illustrate the successful clinical translation of VGT-309 and its potential to improve surgical management of patients undergoing cancer resection [144]. However, VGT0309 has not yet been tested in breast cancer patients.…”
Section: Clinicalmentioning
confidence: 99%
“…In a Phase I clinical trial, VGT-309 was demonstrated to be safe for human use. It is currently in Phase II clinical trials for fluorescence-guided detection of lung cancers . Reports from the first patients were extremely encouraging, with VGT-309 aiding in the identification of nonpalpable lung nodules that were not visually detected by the surgeons.…”
Section: Cysteine Protease Probesmentioning
confidence: 99%